2015
DOI: 10.1007/s10517-015-2845-5
|View full text |Cite
|
Sign up to set email alerts
|

Ischemia in Pelvic Organs as an Independent Pathogenic Factor in the Development of Benign Prostatic Hyperplasia and Urinary Bladder Dysfunction

Abstract: Blood supply to the pelvic organs of outbred male rats was diminished by graduated constriction of the distal part of the inferior vena cava. Deficiency of intramural blood supply in prostate and urinary bladder was revealed by bioimpedance harmonic analysis according to the magnitude of first cardiac peak in the bioimpedance spectrogram. In 1-1.5 months, the histological examination revealed the glandular-stromal form of progressive benign prostatic hyperplasia in all ischemic rats. The development of hyperpl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…The first approach has shown that the bladder vasculature exhibits some degree of plasticity, i.e., the initial reduction of bladder perfusion after iliac artery ligation partly recovers within 4 weeks (Ishida et al 1999). However, changes in perfusion have been shown to influence both structure and function in the lower urinary tract, with a recent study using stenosis of the vena cava in rats observing prostatic enlargement, histological signs of BPH, and urodynamic evidence of bladder overactivity after 4-6 weeks of hypoperfusion (Kirpatovskii et al 2015).…”
Section: Effects Of Chronic Hypoperfusion Of the Bladdermentioning
confidence: 99%
“…The first approach has shown that the bladder vasculature exhibits some degree of plasticity, i.e., the initial reduction of bladder perfusion after iliac artery ligation partly recovers within 4 weeks (Ishida et al 1999). However, changes in perfusion have been shown to influence both structure and function in the lower urinary tract, with a recent study using stenosis of the vena cava in rats observing prostatic enlargement, histological signs of BPH, and urodynamic evidence of bladder overactivity after 4-6 weeks of hypoperfusion (Kirpatovskii et al 2015).…”
Section: Effects Of Chronic Hypoperfusion Of the Bladdermentioning
confidence: 99%
“…This condition is also a multifactorial disorder, strongly associated with ageing, obesity, hypertension, dyslipidemia, diabetic mellitus (DM), and chronic kidney disease (CKD) 1,2 . Although the exact etiologies of OAB remain unclear, one of the believed theories to describe the disease process involves ischemia, vascular damage, and endothelial dysfunction of the bladder 3‐5 . Notably, the presence of OAB is known to be a predictive factor of future cardiovascular events 6,7 …”
Section: Introductionmentioning
confidence: 99%
“…Recently, rats have been widely selected for research into BPH. One rat model involved ligature of the aorta and inferior vena cava . In ligated rats, blood supply to the prostate was decreased and prostate weight subsequently increased.…”
Section: Introductionmentioning
confidence: 99%
“…One rat model involved ligature of the aorta and inferior vena cava. 12 In ligated rats, blood supply to the prostate was decreased and prostate weight subsequently increased. Another model is the spontaneously hypertensive rat (SHR), which is a commonly used model for hypertension and cardiovascular disease.…”
mentioning
confidence: 99%